Enhanced Antitumor Immune Response in 2′-5′ Oligoadenylate Synthetase-Like 1- (OASL1-) Deficient Mice upon Cisplatin Chemotherapy and Radiotherapy - Chan Kyu Sim; Jung Hoon Lee; In-Jeoung Baek; Sang-Wook Lee; Myeong Sup Lee (Journal of Immunology Research)
Type I interferon (IFN-I) plays a critical role in the antitumor immune response. In our previous study, we showed that IFN-I-inducible 2′-5′ oligoadenylate synthetase-like 1 (OASL1) negatively regulated IFN-I production upon tumor challenge similar to that of viral infection. Thus, OASL1-deficient (Oasl1−/−) mice were more resistant to implanted tumor growth than wild-type (WT) mice. In this study, we investigated whether targeting or suppressing OASL1 could show synergistic effects on tumor clearance with conventional cancer therapies (such as chemotherapy and radiotherapy) using Oasl1−/− mice and a transplantable lung metastatic tumor cell model. Upon treatment with the anticancer drug cisplatin, we found that Oasl1−/− mice showed enhanced resistance to injected tumors compared to untreated Oasl1−/− mice. Similarly, irradiated Oasl1−/− mice showed better resistance to tumor challenge than untreated Oasl1−/− mice. Additionally, we found that Oasl1−/− mice applied with both types of the cancer therapies contained more cytotoxic effector cells, such as CD8+ T cells and NK cells, and produced more cytotoxic effector cytokine IFN-γ as well as IFN-I in their tumor-containing lungs compared to untreated Oasl1−/− mice. Collectively, these results show that targeting OASL1 together with conventional cancer therapies could be an effective strategy to enhance treatment efficacy.